2014
DOI: 10.2174/187152571103140120103302
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Resveratrol and Resveratroloside

Abstract: Cardioprotective effect of resveratrol and resveratroloside was determined in ischemia-reperfusion experiments on rats. It was found that single intraperitoneal administration of any compound (10 mg/kg) followed by 30-min ischemia and 120-min reperfusion resulted in statistically significant decrease of myocardial infarct area (55.0±4.0% for control group; 40.7±4.4% for the group 1 received resveratrol; 41.6±4.8% for the group 2 received resveratroloside). The cardioprotective effect of resveratroloside was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Resveratrol, the main compound responsible for “French paradox,” was reported to have multiple health benefits though with some different opinions such as anticancer (Jang and others ), cardioprotective effect (Mokni and others ; Davies and Roulleau ; Naumenko and others ), antidiabetic effects (Szkudelska and Szkudelski ), and skin protection(Bastianetto and others ). Sample 2 (approximately 2.12 mg/g) had significantly higher content in resveratrol 3,5‐ O‐ β‐diglucoside than other species (1‐way ANOVA) and sample 12 had the lowest level of 0.31 mg/g, even though all tree peony seed showed higher content in resveratrol than red wine (approximately 2.9 mg/L).…”
Section: Resultsmentioning
confidence: 99%
“…Resveratrol, the main compound responsible for “French paradox,” was reported to have multiple health benefits though with some different opinions such as anticancer (Jang and others ), cardioprotective effect (Mokni and others ; Davies and Roulleau ; Naumenko and others ), antidiabetic effects (Szkudelska and Szkudelski ), and skin protection(Bastianetto and others ). Sample 2 (approximately 2.12 mg/g) had significantly higher content in resveratrol 3,5‐ O‐ β‐diglucoside than other species (1‐way ANOVA) and sample 12 had the lowest level of 0.31 mg/g, even though all tree peony seed showed higher content in resveratrol than red wine (approximately 2.9 mg/L).…”
Section: Resultsmentioning
confidence: 99%
“…Various investigations have exhibited that resveratrol could benefit T2DM treatment. This compound could enhance insulin sensitivity in patients with T2DM and diabetic rats, reduce blood glucose levels in animals, and protect the pancreatic cells. , Resveratroloside as a monoglucosylated form of resveratrol has been shown to possess antioxidant, antiaging, anti-inflammatory, and antimicrobial , activities and neuroprotective effects. , It has also been demonstrated to have more potent antiallergic and PDE inhibitory activities than those of the corresponding aglycone. , In addition, resveratroloside exhibited a higher cardioprotective effect compared to that of resveratrol . Up to now, studies on the antidiabetic activity of resveratroloside are lacking.…”
Section: Resultsmentioning
confidence: 99%
“…18,20 In addition, resveratroloside exhibited a higher cardioprotective effect compared to that of resveratrol. 31 Up to now, studies on the antidiabetic activity of resveratroloside are lacking.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results indicated that Resveratroloside may greatly improve the area of myocardial infarction (MI) following 30 min of ischemia and 120 min of reperfusion, elucidating Resveratroloside's cardioprotective function (Naumenko et al, 2013).…”
Section: Resveratrolosidementioning
confidence: 99%